OPTIMALISASI PENERIMAAN DAERAH PASCA PENGALIHAN PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN (PBB-P2) DARI PEMERINTAH PUSAT KEPADA PEMERINTAH DAERAH DI KOTA DUMAI - Hildawati Hildawati (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2018)
According to the Constitution No. 28 in 2009 the rural and urban property taxes becomes one of the taxes policy managed by the local government. Dumai local government had just started to implement this rural and urban property taxes policy since January 2013. Dumai local government is an city- level region that has great potential considering the tax economic activities is quite complex . The amount of tax arrears could become potential challenges for the local government of Dumai. This study would describe about the constraints encountered by the local government of Dumai in optimizing the ruraland urban property tax revenue, explaining about the strategies implemented, as well as finding out the level of effectiveness of property tax revenue as the local taxes. It was a descriptive type of study, using interview and documentation record in collecting the data. Purposive technique was used as a basis for selecting the informants, while the data was analyzed by using qualitative and quantitative methods. The results indicated that since the policy of tax revenue was relatively new the problems encountered by the local government of Dumai was in the management, the application of SISMIOP provided by tax Directorate General “Direktorat Jenderal Pajak” could not be implemented well, restricted number of facilities and infrastructure, and lack of human resources capabilities to provide the services. Dumai city government to seek optimization through four things: increasing public awareness , Improved service quality , improving the quality of human resources and the effectiveness of voting